Estudo de contaminantes em águas, sólidos totais suspensos e sedimentos de igarapés da zona urbana de Manaus-Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The study carried out in the contaminated igarapés of the urban zone of the city of Manaus - AM, during the hydrologic periods of drought and flood, showed high concentrations of potentially toxic elements present in the water, total suspended solids and sediments. The objective was to observe the distribution of the elements between the environmental compartments, besides the seasonal and anthropic influences on the presence of these pollutants in the aquatic environments. This work was carried out in 13 points distributed among Mindu, Quarenta, Tarumã and APA - UFAM igarapés (streams that are born in the forest of the UFAM Campus). The elements addressed for discussion on contaminants in this study were Ba , Cd , Cr, Pb , Sb, and Se. For the characterization of the environments under study, the physical-chemical analyzes were carried out together with the analysis of elements in water, total suspended solids and bottom sediments, using ICP-OES and EDX 720 techniques. Chemical measurements and analyzes as described by Standard Methods (APHA 2012), performing classical methods of analysis for pH , temperature and electrical conductivity, turbidity, dissolved oxygen, biological oxygen demand, oxygen chemistry, total suspended solids, nitrogen and phosphorus. The reference standard water quality standard was Resolution 357/2005 of CONAMA, and for the total suspended solids and sediment was used NOAA (National Oceanic and Atmospheric Administration). The Results were statistically analyzed to verify the normal distribution of data, such as the Shapiro - Wilk and Wilcoxon tests, to compare the dry and full hydrological periods. High levels of Ba , Cd , Cr and Pb were observed in all sediments, water, total suspended solids and sediments, demonstrating the relationship of recent contamination with sediment accumulation. The analysis of the principal components showed similarity between the distribution of contaminants in the different streams studied, due to the high concentrations of the determined elements.
Keywords: Poluentes metálicos; Influência urbana; Elementos potencialmente tóxicos; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA